Low-dielectric epoxy resin for copper-clad plate and processing technology of low-dielectric epoxy resin

By adding low-dielectric filler to the epoxy resin for copper clad plate and using low-dielectric curing agent, the problems of high dielectric constant and high brittleness of epoxy resin-based copper clad plate are solved, and low dielectric performance and high toughness are achieved. Combined, it is suitable for 5G communication and other fields.

CN119432011AActive Publication Date: 2025-02-14JIANG SU YAO HONG ELECTRONICS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411562518.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing epoxy resin-based copper clad plate has a high dielectric constant and high brittleness, which limits its application.

Method used

Using low dielectric epoxy resin, the dielectric constant of the epoxy resin is reduced by adding low dielectric filler to component A and using low dielectric curing agent in component B, combined with specific raw material ratios and process steps and Improve its resilience.

Benefits of technology

It achieves low dielectric performance and high toughness of epoxy resin, improves the performance of copper clad plate, and is suitable for 5G communication and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005118264600000101
    Figure BDA0005118264600000101
  • Figure BDA0005118264600000111
    Figure BDA0005118264600000111
Patent Text Reader

Abstract

The invention relates to the field of copper-clad plates, and particularly discloses low-dielectric epoxy resin for a copper-clad plate and a processing technology of the low-dielectric epoxy resin. The low-dielectric epoxy resin for the copper-clad plate comprises a component A and a component B, the component A is prepared from the following raw materials in parts by mass: 100 to 150 parts of acetone, 250 to 300 parts of bisphenol A epoxy resin and 50 to 100 parts of low dielectric filler; the component B comprises the following raw materials in parts by mass: 150-250 parts of a low dielectric curing agent, 20-30 parts of a curing agent and 10-20 parts of a curing accelerator; the preparation method of the low-dielectric curing agent comprises the following steps: stirring a diamine modifier, 4, 4 '-diaminodiphenyl ether, 4, 4'-oxybisphphthalic anhydride and m-cresol under the protection of nitrogen, adding isoquinoline, stirring, cooling, adding m-cresol, discharging in ethanol while hot, washing, filtering, extracting to remove m-cresol, and drying in vacuum to obtain the low-dielectric curing agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of copper clad laminates, and specifically discloses a low-dielectric epoxy resin for copper clad laminates and a processing technology thereof. Background Art

[0002] With the advancement of science and technology, people have higher and higher requirements for information transmission and communication. 5G communication is gradually integrated into production and life. In order to pursue lower signal delay to meet the use requirements of equipment, various smart devices require low dielectric to improve the fidelity of 5G communication.

[0003] Epoxy resin has good mechanical properties, electrical properties, dimensional stability, and adhesion. Epoxy resin-based copper clad laminates have many advantages, but their dielectric constants still need to be reduced. At the same time, due to the chemical structure of epoxy resin, if it is not toughened, it is brittle, which limits its application. Therefore, it is of great significance to study an epoxy resin for copper clad laminates with low dielectric properties and high toughness and its processing technology. Summary of the invention

[0004] The object of the present invention is to provide a low dielectric epoxy resin for copper clad laminate and a processing technology thereof, so as to solve the problems raised in the above background technology.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a low dielectric epoxy resin for copper clad laminates, comprising component A and component B; component A comprises the following raw materials, calculated by mass: 100-150 parts of acetone, 250-300 parts of bisphenol A epoxy resin, and 100-130 parts of low dielectric fillers; component B is a curing component, comprising the following raw materials, calculated by mass: 150-250 parts of low dielectric curing agent, 20-30 parts of curing agent, and 10-20 parts of curing accelerator.

[0006] Preferably, the bisphenol A type epoxy resin includes but is not limited to epoxy resin E44; the curing agent contains an amino group, including but not limited to 2,4-diaminodiphenylamine; and the curing accelerator includes but is not limited to imidazole.

[0007] Preferably, the preparation of the low dielectric curing agent comprises the following steps: taking a diamine modifier, 4,4'-diaminodiphenyl ether, 4,4'-oxydiphthalic anhydride, and m-cresol, stirring under nitrogen protection, adding isoquinoline, stirring, adding m-cresol after cooling, discharging the material into ethanol while hot, washing, filtering, extracting to remove m-cresol, and vacuum drying to obtain a low dielectric curing agent.

[0008] Preferably, the low dielectric curing agent comprises the following raw materials, by mass: 3 to 8 parts of diamine modifier, 8 to 15 parts of 4,4'-diaminodiphenyl ether, 20 to 30 parts of 4,4'-oxydiphthalic anhydride, 200 to 300 parts of m-cresol, 10 to 20 parts of isoquinoline, and 600 to 800 parts of ethanol.

[0009] Preferably, the preparation of the diamine modifier comprises the following steps: S1: taking 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane, stirring evenly, and configuring solution A; taking undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and propylene glycol, mixing evenly, and configuring solution B; taking trichloronitrobenzene, potassium carbonate A, and methanol, mixing evenly, cooling to 0-1°C, adding solution A dropwise thereto under nitrogen protection, stirring and heating to reflux for 20-25h, adding potassium carbonate B, cooling to 0-1°C, adding solution B dropwise thereto under nitrogen protection, stirring and heating to reflux for 25-30h, cooling to room temperature, sinking in saturated sodium chloride ice water solution, and collecting solid by suction; recrystallizing the obtained solid with methanol, filtering and drying to obtain substance A;

[0010] S2: Take ammonium formate and ethanol, stir evenly to obtain solution C; add substance A, palladium carbon catalyst, and 1,4-dioxane, stir evenly, heat to reflux, slowly drip solution C, reflux and stir for 20 to 25 hours, filter while hot to remove the palladium carbon catalyst, add saturated sodium chloride ice water solution, dry, and perform column chromatography to obtain a diamine modifier.

[0011] Preferably, the diamine modifier comprises the following raw materials, in parts by mass: 20 to 30 parts of substance A, 0.5 to 2 parts of palladium-carbon catalyst, 80 to 150 parts of 1,4-dioxane, and 80 to 150 parts of solution C; in substance A, the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole is (1 to 1.5): (1 to 1.5): 1: 1, the mass of potassium carbonate A is 10 to 15% of the mass of trichloronitrobenzene, and the mass of methanol is 6 to 8 times that of trichloronitrobenzene; the mass of potassium carbonate B is 15 to 25% of the mass of undecyl alcohol.

[0012] Preferably, the solution A comprises 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:(8-12); the solution B comprises undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and propylene glycol in an amount of 8-12 times the total mass of undecyl alcohol and 4-hydroxy-3-tert-butyl-anisole; and the solution C comprises ammonium formate and ethanol in a mass ratio of 1:(4-5).

[0013] Preferably, the preparation of the low dielectric filler includes the following steps: adding hollow glass microspheres to an aqueous sodium hydroxide solution, reflux stirring and reacting for 1 to 2 hours, washing until neutral, drying, adding an ethanol aqueous solution and an aminosilane coupling agent, stirring at 70 to 80° C. for 4 to 6 hours, filtering, washing with water, and drying to obtain an amino-modified filler; taking the amino-modified filler, acetone, and 1,6-hexanediol diglycidyl ether, mixing them evenly, reflux reacting for 6 to 8 hours, removing the solvent, washing, and drying to obtain a low dielectric filler.

[0014] Preferably, the concentration of the sodium hydroxide aqueous solution is 0.3 mol / L; in the ethanol aqueous solution, the volume ratio of ethanol to water is (6-8):1; and the aminosilane coupling agent is KH550.

[0015] Preferably, the low dielectric filler comprises the following raw materials, calculated by mass: 10 to 20 parts of amino-modified filler, 100 to 150 parts of acetone, and 3 to 8 parts of 1,6-hexanediol diglycidyl ether; in the amino-modified filler, the amount of ethanol aqueous solution added is 8 to 12 times the mass of the hollow glass microspheres, and the amount of aminosilane coupling agent added is 5 to 10% of the mass of the hollow glass microspheres; the concentration of the hollow glass microspheres in the sodium hydroxide aqueous solution is 0.03 to 0.05 mg / mL.

[0016] Preferably, the processing technology of a low dielectric epoxy resin for copper clad laminates described in any one of the above items comprises the following steps: taking acetone and bisphenol A epoxy resin, mixing them evenly, adding a low dielectric filler, stirring evenly, and obtaining component A; taking a low dielectric curing agent, a curing agent, and a curing accelerator, stirring for 3 to 5 minutes, and obtaining component B; adding component B to component A, mixing evenly, and obtaining a low dielectric epoxy resin for copper clad laminates.

[0017] Compared with the prior art, the beneficial effects achieved by the present invention are as follows: a low dielectric epoxy resin for copper clad laminate is prepared, comprising component A and component B; a low dielectric filler is added to component A, the filler is obtained by modifying hollow glass microspheres with amino groups with 1,6-hexanediol diglycidyl ether, the hollow glass microspheres have a hollow structure, and the dielectric constant of the epoxy resin can be greatly reduced after being added; 1,6-hexanediol diglycidyl ether is an active diluent, and its introduction can improve the processability of the epoxy resin; because it contains a flexible chain segment, the toughness of the epoxy resin can be improved, and the polarization degree can be reduced, which is beneficial to the reduction of the dielectric constant; the modification also introduces epoxy groups into the hollow glass microspheres, thereby improving the compatibility of the hollow glass microspheres with the epoxy resin and component B.

[0018] Component B includes a low dielectric curing agent, a curing agent, and a curing accelerator. The low dielectric curing agent is prepared from a diamine modifier, 4,4'-diaminodiphenyl ether, and 4,4'-oxydiphthalic anhydride. During the preparation process, a large amount of 4,4'-oxydiphthalic anhydride is added. Therefore, the two ends of the low dielectric modifier are active carboxylic anhydride groups. Compared with the amino-cured epoxy resin, the structure generated when the anhydride cures the epoxy resin has a lower polarity, which helps to reduce the dielectric constant; the raw materials of the diamine modifier include undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene, and 1-methyl-5-nitro-2-hydroxymethylimidazole in a molar ratio of (1 to 1.5): (1 to 1.5): 1:1. First, the -OH in 1-methyl-5-nitro-2-hydroxymethylimidazole reacts with a -Cl of trichloronitrobenzene, and then undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole and another -Cl is reacted to obtain substance A, and then -NO2 is converted into -NH2 through modification to obtain a diamine modifier; among them, the imidazole structure of 1-methyl-5-nitro-2-hydroxymethylimidazole can improve heat resistance and water resistance, and also has a positive effect on improving the toughness of epoxy resin and reducing the dielectric constant; 4-hydroxy-3-tert-butyl-anisole contains tert-butyl, and the introduction of tert-butyl can effectively reduce the dielectric constant. At the same time, the anisole structure also helps to improve the performance of epoxy resin; while improving the fluidity and processability of epoxy resin, the long chain of undecyl alcohol helps to improve the brittleness of epoxy resin and improve the tensile properties; introducing the above three substances in a certain proportion can effectively improve the toughness of epoxy resin and reduce the dielectric constant; the low dielectric curing agent prepared by this method is used in combination with traditional amino curing agent and curing accelerator, which not only gives epoxy resin excellent performance, but also improves the curing efficiency. DETAILED DESCRIPTION

[0019] The following is a preferred implementation of the embodiment of the present invention. Obviously, the described embodiment is only a part of the embodiment of the present invention, not all of the embodiments. For ordinary technicians in this technical field, all other embodiments obtained by ordinary technicians in this field without creative work without departing from the principle of the embodiment of the present invention are within the scope of protection of the present invention.

[0020] The following parts are by mass unless otherwise specified;

[0021] Example 1: S1: Take 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:10, stir evenly, and prepare solution A; take undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and propylene glycol with a mass of 10 times that of both, mix evenly, and prepare solution B; take trichloronitrobenzene, potassium carbonate A, and methanol, cool to 0°C, add solution A dropwise thereto under nitrogen protection, stir and heat under reflux for 22h, add potassium carbonate B, cool to 0°C, add solution B dropwise thereto under nitrogen protection, stir and heat Reflux for 26 hours, cool to room temperature, sink in 500 parts of saturated sodium chloride ice water solution, and collect the solid by suction filtration; the obtained solid is recrystallized with methanol, filtered and dried to obtain substance A; the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole is 1.2:1.2:1:1, the mass of potassium carbonate A is 12% of the mass of trichloronitrobenzene, and the mass of methanol is 7 times that of trichloronitrobenzene; the mass of potassium carbonate B is 24% of the mass of undecyl alcohol;

[0022] S2: Take ammonium formate and ethanol in a mass ratio of 1:5, stir evenly to obtain solution C; add 25 parts of substance A, 1 part of palladium carbon catalyst, and 120 parts of 1,4-dioxane, stir evenly, heat to reflux, slowly drip 120 parts of solution C, reflux and stir for 24 hours; filter while hot to remove the palladium carbon catalyst, add 500 parts of saturated sodium chloride ice water solution, dry, and then perform column chromatography with dichloromethane and ethyl acetate in a volume ratio of 1:1 to obtain a diamine modifier;

[0023] S3: Add 6 parts of diamine modifier, 12 parts of 4,4'-diaminodiphenyl ether, 25 parts of 4,4'-oxydiphthalic anhydride, and 250 parts of m-cresol, stir at 80°C for 7 hours under nitrogen protection, add 15 parts of isoquinoline, stir at 115°C for 8 hours, stir at 180°C for 12 hours, cool to 90°C, add 10 parts of m-cresol, discharge while hot into 800 parts of anhydrous ethanol, wash, filter, extract to remove m-cresol, and dry in vacuo at 120°C for 20 hours to obtain a low dielectric curing agent;

[0024] S4: adding the hollow glass microspheres to a sodium hydroxide aqueous solution with a concentration of 0.3 mol / L, reflux stirring for reaction for 2 h, washing to neutrality, drying, adding an ethanol aqueous solution with a mass of 12 times that of the hollow glass microspheres and KH550 with a mass of 8% of the hollow glass microspheres, stirring at 80°C for 6 h, filtering, washing with water, and drying to obtain an amino-modified filler; the volume ratio of ethanol to water in the ethanol aqueous solution is 8:1; the concentration of the hollow glass microspheres in the sodium hydroxide solution is 0.03 mg / mL;

[0025] S5: Take 15 parts of amino-modified filler, 150 parts of acetone, and 6 parts of 1,6-hexanediol diglycidyl ether, mix them evenly, reflux for 8 hours, remove the solvent, wash, and dry to obtain a low dielectric filler;

[0026] S6: Take 130 parts of acetone and 250 parts of bisphenol A epoxy resin, mix them evenly, add 120 parts of low dielectric filler, stir evenly, and obtain component A; take 220 parts of low dielectric curing agent, 20 parts of curing agent 2,4-diaminodiphenylamine, and 10 parts of curing accelerator imidazole, stir to obtain component B; mix component B with component A to obtain low dielectric epoxy resin for copper clad laminate.

[0027] Example 2: S1: Take 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:10, stir evenly, and prepare solution A; take undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and 10 times the mass of propylene glycol, mix evenly, and prepare solution B; take trichloronitrobenzene, potassium carbonate A, and methanol, cool to 0°C, add solution A dropwise thereto under nitrogen protection, stir and heat under reflux for 22h, add potassium carbonate B, cool to 0°C, add solution B dropwise thereto under nitrogen protection, stir and heat Reflux for 26 hours, cool to room temperature, sink in 500 parts of saturated sodium chloride ice water solution, and collect solid by suction filtration; recrystallize the obtained solid with methanol, filter and dry to obtain substance A; the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole is 1:1.5:1:1, the mass of potassium carbonate A is 12% of the mass of trichloronitrobenzene, and the mass of methanol is 7 times that of trichloronitrobenzene; the mass of potassium carbonate B is 24% of the mass of undecyl alcohol;

[0028] S2: Take ammonium formate and ethanol in a mass ratio of 1:5, stir evenly to obtain solution C; add 20 parts of substance A, 0.5 parts of palladium carbon catalyst, and 80 parts of 1,4-dioxane, stir evenly, heat to reflux, slowly drip 80 parts of solution C, reflux and stir for 24 hours; filter while hot to remove the palladium carbon catalyst, add 500 parts of saturated sodium chloride ice water solution, dry, and then perform column chromatography with dichloromethane and ethyl acetate in a volume ratio of 1:1 to obtain a diamine modifier;

[0029] S3: Add 3 parts of diamine modifier, 8 parts of 4,4'-diaminodiphenyl ether, 20 parts of 4,4'-oxydiphthalic anhydride, and 250 parts of m-cresol, stir at 80°C for 7 hours under nitrogen protection, add 10 parts of isoquinoline, stir at 115°C for 8 hours, stir at 180°C for 12 hours, cool to 90°C, add 10 parts of m-cresol, discharge while hot into 800 parts of anhydrous ethanol, wash, filter, extract to remove m-cresol, and dry in vacuo at 120°C for 20 hours to obtain a low dielectric curing agent;

[0030] S4: adding the hollow glass microspheres to a sodium hydroxide aqueous solution with a concentration of 0.3 mol / L, reflux stirring for reaction for 2 h, washing to neutrality, drying, adding an ethanol aqueous solution with a mass of 12 times that of the hollow glass microspheres and KH550 with a mass of 5% of the hollow glass microspheres, stirring at 80°C for 6 h, filtering, washing with water, and drying to obtain an amino-modified filler; the volume ratio of ethanol to water in the ethanol aqueous solution is 8:1; the concentration of the hollow glass microspheres in the sodium hydroxide solution is 0.03 mg / mL;

[0031] S5: Take 10 parts of amino-modified filler, 150 parts of acetone, and 3 parts of 1,6-hexanediol diglycidyl ether, mix them evenly, reflux for 8 hours, remove the solvent, wash, and dry to obtain a low dielectric filler;

[0032] S6: Take 130 parts of acetone and 250 parts of bisphenol A epoxy resin, mix them evenly, add 120 parts of low dielectric filler, stir evenly, and obtain component A; take 220 parts of low dielectric curing agent, 20 parts of curing agent 2,4-diaminodiphenylamine, and 10 parts of curing accelerator imidazole, stir to obtain component B; mix component B with component A to obtain low dielectric epoxy resin for copper clad laminate.

[0033] Example 3: S1: Take 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:10, stir evenly, and prepare solution A; take undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and 10 times the mass of propylene glycol, mix evenly, and prepare solution B; take trichloronitrobenzene, potassium carbonate A, and methanol, cool to 0°C, add solution A dropwise thereto under nitrogen protection, stir and heat under reflux for 22h, add potassium carbonate B, cool to 0°C, add solution B dropwise thereto under nitrogen protection, stir and heat Reflux for 26 hours, cool to room temperature, sink in 500 parts of saturated sodium chloride ice water solution, and collect solid by suction filtration; recrystallize the obtained solid with methanol, filter and dry to obtain substance A; the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole is 1.5:1:1:1, the mass of potassium carbonate A is 12% of the mass of trichloronitrobenzene, and the mass of methanol is 7 times that of trichloronitrobenzene; the mass of potassium carbonate B is 24% of the mass of undecyl alcohol;

[0034] S2: Take ammonium formate and ethanol in a mass ratio of 1:5, stir evenly to obtain solution C; add 30 parts of substance A, 2 parts of palladium carbon catalyst, and 150 parts of 1,4-dioxane, stir evenly, heat to reflux, slowly drip 150 parts of solution C, reflux and stir for 24 hours; filter while hot to remove the palladium carbon catalyst, add 500 parts of saturated sodium chloride ice water solution, dry, and then perform column chromatography with dichloromethane and ethyl acetate in a volume ratio of 1:1 to obtain a diamine modifier;

[0035] S3: Add 8 parts of diamine modifier, 15 parts of 4,4'-diaminodiphenyl ether, 30 parts of 4,4'-oxydiphthalic anhydride, and 250 parts of m-cresol, stir at 80°C for 7 hours under nitrogen protection, add 20 parts of isoquinoline, stir at 115°C for 8 hours, stir at 180°C for 12 hours, cool to 90°C, add 10 parts of m-cresol, discharge while hot into 800 parts of anhydrous ethanol, wash, filter, extract to remove m-cresol, and vacuum dry at 120°C for 20 hours to obtain a low dielectric curing agent;

[0036] S4: adding the hollow glass microspheres to a sodium hydroxide aqueous solution with a concentration of 0.3 mol / L, reflux stirring for reaction for 2 h, washing to neutrality, drying, adding an ethanol aqueous solution with a mass of 12 times that of the hollow glass microspheres and KH550 with a mass of 10% of the hollow glass microspheres, stirring at 80°C for 6 h, filtering, washing with water, and drying to obtain an amino-modified filler; the volume ratio of ethanol to water in the ethanol aqueous solution is 8:1; the concentration of the hollow glass microspheres in the sodium hydroxide solution is 0.03 mg / mL;

[0037] S5: Take 20 parts of amino-modified filler, 150 parts of acetone, and 8 parts of 1,6-hexanediol diglycidyl ether, mix them evenly, reflux for 8 hours, remove the solvent, wash, and dry to obtain a low dielectric filler;

[0038] S6: Take 130 parts of acetone and 250 parts of bisphenol A epoxy resin, mix them evenly, add 120 parts of low dielectric filler, stir evenly, and obtain component A; take 220 parts of low dielectric curing agent, 20 parts of curing agent 2,4-diaminodiphenylamine, and 10 parts of curing accelerator imidazole, stir to obtain component B; mix component B with component A to obtain low dielectric epoxy resin for copper clad laminate.

[0039] Comparative Example 1 (changing the amount of diamine modifier, 4,4'-diaminodiphenyl ether, and 4,4'-oxydiphthalic anhydride, and the other method steps are consistent with Example 1): S1: Take 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:10, stir evenly, and configure into solution A; take undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and 10 times the mass of propylene glycol, mix evenly, and configure into solution B; take trichloronitrobenzene, potassium carbonate A, and methanol, cool to 0°C, add solution A dropwise thereto under nitrogen protection, stir and heat under reflux for 22 hours, and add potassium carbonate B , cooled to 0°C, solution B was added dropwise thereto under nitrogen protection, stirred and heated under reflux for 26 hours, cooled to room temperature, precipitated in 500 parts of saturated sodium chloride ice water solution, and solids were collected by suction filtration; the obtained solid was recrystallized with methanol, filtered and dried to obtain substance A; the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole was 1.2:1.2:1:1, the mass of potassium carbonate A was 12% of the mass of trichloronitrobenzene, the mass of methanol was 7 times that of trichloronitrobenzene; the mass of potassium carbonate B was 24% of the mass of undecyl alcohol;

[0040] S2: Take ammonium formate and ethanol in a mass ratio of 1:5, stir evenly to obtain solution C; add 25 parts of substance A, 1 part of palladium carbon catalyst, and 120 parts of 1,4-dioxane, stir evenly, heat to reflux, slowly drip 120 parts of solution C, reflux and stir for 24 hours; filter while hot to remove the palladium carbon catalyst, add 500 parts of saturated sodium chloride ice water solution, dry, and then perform column chromatography with dichloromethane and ethyl acetate in a volume ratio of 1:1 to obtain a diamine modifier;

[0041] S3: Add 12 parts of diamine modifier, 24 parts of 4,4'-diaminodiphenyl ether, 10 parts of 4,4'-oxydiphthalic anhydride, and 250 parts of m-cresol, stir at 80°C for 7 hours under nitrogen protection, add 15 parts of isoquinoline, stir at 115°C for 8 hours, stir at 180°C for 12 hours, cool to 90°C, add 10 parts of m-cresol, discharge while hot into 800 parts of anhydrous ethanol, wash, filter, extract to remove m-cresol, and dry in vacuo at 120°C for 20 hours to obtain a low dielectric curing agent;

[0042] S4: adding the hollow glass microspheres to a sodium hydroxide aqueous solution with a concentration of 0.3 mol / L, reflux stirring for reaction for 2 h, washing to neutrality, drying, adding an ethanol aqueous solution with a mass of 12 times that of the hollow glass microspheres and KH550 with a mass of 8% of the hollow glass microspheres, stirring at 80°C for 6 h, filtering, washing with water, and drying to obtain an amino-modified filler; the volume ratio of ethanol to water in the ethanol aqueous solution is 8:1; the concentration of the hollow glass microspheres in the sodium hydroxide solution is 0.03 mg / mL;

[0043] S5: Take 15 parts of amino-modified filler, 150 parts of acetone, and 6 parts of 1,6-hexanediol diglycidyl ether, mix them evenly, reflux for 8 hours, remove the solvent, wash, and dry to obtain a low dielectric filler;

[0044] S6: Take 130 parts of acetone and 250 parts of bisphenol A epoxy resin, mix them evenly, add 120 parts of low dielectric filler, stir evenly, and obtain component A; take 220 parts of low dielectric curing agent, 20 parts of curing agent 2,4-diaminodiphenylamine, and 10 parts of curing accelerator imidazole, stir to obtain component B; mix component B with component A to obtain low dielectric epoxy resin for copper clad laminate.

[0045] Comparative Example 2 (changing the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole, and the remaining method steps are consistent with Example 1): S1: Take 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:10, stir evenly, and prepare solution A; take undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and propylene glycol 10 times the mass of both, mix evenly, and prepare solution B; take trichloronitrobenzene, potassium carbonate A, and methanol, cool to 0°C, add solution A dropwise thereto under nitrogen protection, stir and heat under reflux for 2 hours 2h, potassium carbonate B was added, cooled to 0°C, solution B was added dropwise thereto under nitrogen protection, stirred and heated under reflux for 26h, cooled to room temperature, precipitated in 500 parts of saturated sodium chloride ice water solution, and solid was collected by suction filtration; the obtained solid was recrystallized with methanol, filtered and dried to obtain substance A; the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole was 1:2:1:2, the mass of potassium carbonate A was 12% of the mass of trichloronitrobenzene, the mass of methanol was 7 times that of trichloronitrobenzene; the mass of potassium carbonate B was 24% of the mass of undecyl alcohol;

[0046] S2: Take ammonium formate and ethanol in a mass ratio of 1:5, stir evenly to obtain solution C; add 25 parts of substance A, 1 part of palladium carbon catalyst, and 120 parts of 1,4-dioxane, stir evenly, heat to reflux, slowly drip 120 parts of solution C, reflux and stir for 24 hours; filter while hot to remove the palladium carbon catalyst, add 500 parts of saturated sodium chloride ice water solution, dry, and then perform column chromatography with dichloromethane and ethyl acetate in a volume ratio of 1:1 to obtain a diamine modifier;

[0047] S3: Add 6 parts of diamine modifier, 12 parts of 4,4'-diaminodiphenyl ether, 25 parts of 4,4'-oxydiphthalic anhydride, and 250 parts of m-cresol, stir at 80°C for 7 hours under nitrogen protection, add 15 parts of isoquinoline, stir at 115°C for 8 hours, stir at 180°C for 12 hours, cool to 90°C, add 10 parts of m-cresol, discharge while hot into 800 parts of anhydrous ethanol, wash, filter, extract to remove m-cresol, and dry in vacuo at 120°C for 20 hours to obtain a low dielectric curing agent;

[0048] S4: adding the hollow glass microspheres to a sodium hydroxide aqueous solution with a concentration of 0.3 mol / L, reflux stirring for reaction for 2 h, washing to neutrality, drying, adding an ethanol aqueous solution with a mass of 12 times that of the hollow glass microspheres and KH550 with a mass of 8% of the hollow glass microspheres, stirring at 80°C for 6 h, filtering, washing with water, and drying to obtain an amino-modified filler; the volume ratio of ethanol to water in the ethanol aqueous solution is 8:1; the concentration of the hollow glass microspheres in the sodium hydroxide solution is 0.03 mg / mL;

[0049] S5: Take 15 parts of amino-modified filler, 150 parts of acetone, and 6 parts of 1,6-hexanediol diglycidyl ether, mix them evenly, reflux for 8 hours, remove the solvent, wash, and dry to obtain a low dielectric filler;

[0050] S6: Take 130 parts of acetone and 250 parts of bisphenol A epoxy resin, mix them evenly, add 120 parts of low dielectric filler, stir evenly, and obtain component A; take 220 parts of low dielectric curing agent, 20 parts of curing agent 2,4-diaminodiphenylamine, and 10 parts of curing accelerator imidazole, stir to obtain component B; mix component B with component A to obtain low dielectric epoxy resin for copper clad laminate.

[0051] Comparative Example 3 (amino-modified filler replaces low dielectric filler, and the remaining method steps are consistent with Example 1): S1: Take 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:10, stir evenly, and prepare solution A; take undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and 10 times the mass of propylene glycol, mix evenly, and prepare solution B; take trichloronitrobenzene, potassium carbonate A, and methanol, cool to 0°C, add solution A dropwise thereto under nitrogen protection, stir and heat under reflux for 22h, add potassium carbonate B, cool to 0°C, and protect with nitrogen Solution B was added dropwise thereto, the mixture was stirred and heated under reflux for 26 hours, cooled to room temperature, and precipitated in 500 parts of saturated sodium chloride ice water solution, and the solid was collected by suction filtration; the obtained solid was recrystallized with methanol, filtered and dried to obtain substance A; the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole was 1.2:1.2:1:1, the mass of potassium carbonate A was 12% of the mass of trichloronitrobenzene, the mass of methanol was 7 times that of trichloronitrobenzene; the mass of potassium carbonate B was 24% of the mass of undecyl alcohol;

[0052] S2: Take ammonium formate and ethanol in a mass ratio of 1:5, stir evenly to obtain solution C; add 25 parts of substance A, 1 part of palladium carbon catalyst, and 120 parts of 1,4-dioxane, stir evenly, heat to reflux, slowly drip 120 parts of solution C, reflux and stir for 24 hours; filter while hot to remove the palladium carbon catalyst, add 500 parts of saturated sodium chloride ice water solution, dry, and then perform column chromatography with dichloromethane and ethyl acetate in a volume ratio of 1:1 to obtain a diamine modifier;

[0053] S3: Add 6 parts of diamine modifier, 12 parts of 4,4'-diaminodiphenyl ether, 25 parts of 4,4'-oxydiphthalic anhydride, and 250 parts of m-cresol, stir at 80°C for 7 hours under nitrogen protection, add 15 parts of isoquinoline, stir at 115°C for 8 hours, stir at 180°C for 12 hours, cool to 90°C, add 10 parts of m-cresol, discharge while hot into 800 parts of anhydrous ethanol, wash, filter, extract to remove m-cresol, and dry in vacuo at 120°C for 20 hours to obtain a low dielectric curing agent;

[0054] S4: adding the hollow glass microspheres to a sodium hydroxide aqueous solution with a concentration of 0.3 mol / L, reflux stirring for reaction for 2 h, washing to neutrality, drying, adding an ethanol aqueous solution with a mass of 12 times that of the hollow glass microspheres and KH550 with a mass of 8% of the hollow glass microspheres, stirring at 80°C for 6 h, filtering, washing with water, and drying to obtain an amino-modified filler; the volume ratio of ethanol to water in the ethanol aqueous solution is 8:1; the concentration of the hollow glass microspheres in the sodium hydroxide solution is 0.03 mg / mL;

[0055] S5: Take 130 parts of acetone and 250 parts of bisphenol A epoxy resin, mix them evenly, add 120 parts of low dielectric filler, stir evenly, and obtain component A; take 220 parts of low dielectric curing agent, 20 parts of curing agent 2,4-diaminodiphenylamine, and 10 parts of curing accelerator imidazole, stir, and obtain component B; mix component B with component A to obtain low dielectric epoxy resin for copper clad laminate.

[0056] Comparative Example 4 (changing the amount of raw materials in component A and component B, the other method steps are consistent with Example 1): S1: Take 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:10, stir evenly, and configure into solution A; take undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and 10 times the mass of propylene glycol, mix evenly, and configure into solution B; take trichloronitrobenzene, potassium carbonate A, and methanol, cool to 0°C, add solution A dropwise thereto under nitrogen protection, stir and heat under reflux for 22h, add potassium carbonate B, cool to 0°C, and nitrogen protection Solution B was added dropwise thereto under protection, the mixture was heated under stirring and refluxed for 26 hours, cooled to room temperature, and precipitated in 500 parts of saturated sodium chloride ice water solution, and the solid was collected by suction filtration; the obtained solid was recrystallized with methanol, filtered and dried to obtain substance A; the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole was 1.2:1.2:1:1, the mass of potassium carbonate A was 12% of the mass of trichloronitrobenzene, the mass of methanol was 7 times that of trichloronitrobenzene; the mass of potassium carbonate B was 24% of the mass of undecyl alcohol;

[0057] S2: Take ammonium formate and ethanol in a mass ratio of 1:5, stir evenly to obtain solution C; add 25 parts of substance A, 1 part of palladium carbon catalyst, and 120 parts of 1,4-dioxane, stir evenly, heat to reflux, slowly drip 120 parts of solution C, reflux and stir for 24 hours; filter while hot to remove the palladium carbon catalyst, add 500 parts of saturated sodium chloride ice water solution, dry, and then perform column chromatography with dichloromethane and ethyl acetate in a volume ratio of 1:1 to obtain a diamine modifier;

[0058] S3: Add 6 parts of diamine modifier, 12 parts of 4,4'-diaminodiphenyl ether, 25 parts of 4,4'-oxydiphthalic anhydride, and 250 parts of m-cresol, stir at 80°C for 7 hours under nitrogen protection, add 15 parts of isoquinoline, stir at 115°C for 8 hours, stir at 180°C for 12 hours, cool to 90°C, add 10 parts of m-cresol, discharge while hot into 800 parts of anhydrous ethanol, wash, filter, extract to remove m-cresol, and dry in vacuo at 120°C for 20 hours to obtain a low dielectric curing agent;

[0059] S4: adding the hollow glass microspheres to a sodium hydroxide aqueous solution with a concentration of 0.3 mol / L, reflux stirring for reaction for 2 h, washing to neutrality, drying, adding an ethanol aqueous solution with a mass of 12 times that of the hollow glass microspheres and KH550 with a mass of 8% of the hollow glass microspheres, stirring at 80°C for 6 h, filtering, washing with water, and drying to obtain an amino-modified filler; the volume ratio of ethanol to water in the ethanol aqueous solution is 8:1; the concentration of the hollow glass microspheres in the sodium hydroxide solution is 0.03 mg / mL;

[0060] S5: Take 15 parts of amino-modified filler, 150 parts of acetone, and 6 parts of 1,6-hexanediol diglycidyl ether, mix them evenly, reflux for 8 hours, remove the solvent, wash, and dry to obtain a low dielectric filler;

[0061] S6: Take 130 parts of acetone and 250 parts of bisphenol A epoxy resin, mix them evenly, add 150 parts of low dielectric filler, stir evenly, and obtain component A; take 260 parts of low dielectric curing agent, 20 parts of curing agent 2,4-diaminodiphenylamine, and 10 parts of curing accelerator imidazole, stir to obtain component B; mix component B with component A to obtain low dielectric epoxy resin for copper clad laminate.

[0062] In the above embodiments, the test methods used are conventional methods unless otherwise specified; the raw materials used are commercially available unless otherwise specified, and the sources of the raw materials are as follows: ethanol (CAS: 64-17-5); 1-methyl-5-nitro-2-hydroxymethylimidazole (CAS: 936-05-0); dichloromethane (CAS: 75-09-2); undecyl alcohol (CAS: 112-42-5); 4-hydroxy-3-tert-butyl-anisole (CAS: 121-00-6); propylene glycol (CAS: 57-55-6); trichloronitrobenzene (CAS: 29595-61-7); methanol (CAS: 67-56-1); ammonium formate (CAS: 540-69-2); palladium-carbon catalyst (5%, Xi'an Kaili New Materials Co., Ltd.); 1,4-dioxane (CAS: 123-91-1); ethyl acetate ( CAS: 141-78-6); 4,4'-diaminodiphenyl ether (CAS: 101-80-4); 4,4'-oxydiphthalic anhydride (CAS: 1823-59-2); m-cresol (CAS: 108-39-4); isoquinoline (CAS: 119-65-3); hollow glass microspheres (~40μm, Kramar); silane coupling agent (KH550, S15028, Shanghai Yuanye) ; 1,6-hexanediol diglycidyl ether (CAS: 16096-31-4); bisphenol A epoxy resin (E44, epoxy equivalent 210-240 g / eq, Nanjing Bermuda Biotechnology Co., Ltd.); 2,4-diaminodiphenylamine (CAS: 136-17-4); imidazole (CAS: 288-32-4); potassium carbonate (S3039, Shanghai Yuanye); acetone (CAS: 67-64-1).

[0063] Experiment: Component B and component A prepared in Examples 1 to 3 and Comparative Examples 1 to 4 were mixed; (1) cured in a mold with a diameter of 11 cm and a thickness of 5 mm, under the conditions of 70° C. for 1 h and 150° C. for 4 h; then the dielectric constant was tested using an Aiyi QBG-3D tester; (2) after curing according to the above steps, the tensile strength was tested in accordance with the GB / T1843-2008 standard; the specific data are shown in the table below;

[0064]

[0065]

[0066] Conclusion: In Comparative Example 1, the amount of diamine modifier, 4,4'-diaminodiphenyl ether, and 4,4'-oxydiphthalic anhydride is changed. Since the amount of 4,4'-oxydiphthalic anhydride is reduced, the end of the low dielectric curing agent is an amino group, and the dielectric constant is increased compared with the epoxy resin cured with anhydride in the embodiment; Comparative Example 2 changes the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole, resulting in a reduction in the amount of undecyl alcohol introduced, and the reduction in long chains leads to a decrease in toughness, so the tensile strength is significantly reduced; Comparative Example 3 replaces the low dielectric filler with an amino-modified filler, that is, 1,6-hexanediol diglycidyl ether is not introduced, and the performance is not as good as the embodiment; Comparative Example 4 The amount of low dielectric filler and low dielectric curing agent added is increased, and the tensile properties are significantly reduced; In summary, the low dielectric epoxy resin for copper clad laminates prepared by the present invention has a low dielectric constant and good tensile properties, and has good practical value.

[0067] Finally, it should be noted that the above is only a preferred embodiment of the present invention, but the protection scope of this application is not limited thereto. Any changes or substitutions that can be easily thought of by any technician familiar with the technical field within the spirit and principle of the present invention and within the technical scope disclosed in this application should be included in the protection scope of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other. Therefore, the protection scope of this application shall be based on the protection scope of the claims.

Claims

1. A low dielectric epoxy resin for copper clad laminate, characterized in that: It includes component A and component B; component A includes the following raw materials, calculated by weight: 100-150 parts of acetone, 250-300 parts of bisphenol A epoxy resin, and 100-130 parts of low dielectric filler; component B is a curing component, including the following raw materials, calculated by weight: 150-250 parts of low dielectric curing agent, 20-30 parts of curing agent, and 10-20 parts of curing accelerator.

2. The low dielectric epoxy resin for copper clad laminate according to claim 1, characterized in that: The preparation of the low dielectric curing agent comprises the following steps: taking a diamine modifier, 4,4'-diaminodiphenyl ether, 4,4'-oxydiphthalic anhydride and m-cresol, stirring under nitrogen protection, adding isoquinoline, stirring, adding m-cresol after cooling, discharging the material while hot into ethanol, washing, filtering, extracting to remove m-cresol, and vacuum drying to obtain a low dielectric curing agent.

3. The low dielectric epoxy resin for copper clad laminate according to claim 2, characterized in that: The low dielectric curing agent comprises the following raw materials, calculated by weight: 3 to 8 parts of diamine modifier, 8 to 15 parts of 4,4'-diaminodiphenyl ether, 20 to 30 parts of 4,4'-oxydiphthalic anhydride, 200 to 300 parts of meta-cresol, 10 to 20 parts of isoquinoline, and 600 to 800 parts of ethanol.

4. The low dielectric epoxy resin for copper clad laminate according to claim 2, characterized in that: Preparation of the diamine modifier The following steps are involved: S1: Take 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane, stir evenly to prepare solution A; take undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and propylene glycol, mix evenly to prepare solution B; take trichloronitrobenzene, potassium carbonate A, and methanol, mix evenly, cool to 0-1°C, add solution A dropwise thereto under nitrogen protection, stir and heat under reflux for 20-25h, add potassium carbonate B, cool to 0-1°C, add solution B dropwise thereto under nitrogen protection, stir and heat under reflux for 25-30h, cool to room temperature, sink in saturated sodium chloride ice water solution, and collect solid by suction; recrystallize the obtained solid with methanol, filter and dry it to obtain substance A; S2: Take ammonium formate and ethanol, stir evenly to obtain solution C; add substance A, palladium carbon catalyst, and 1,4-dioxane, stir evenly, heat to reflux, slowly drip solution C, reflux and stir for 20 to 25 hours, filter while hot to remove the palladium carbon catalyst, add saturated sodium chloride ice water solution, dry, and perform column chromatography to obtain a diamine modifier.

5. The low dielectric epoxy resin for copper clad laminate according to claim 4, characterized in that: The diamine modifier comprises the following raw materials, calculated by weight: 20 to 30 parts of substance A, 0.5 to 2 parts of palladium-carbon catalyst, 80 to 150 parts of 1,4-dioxane, and 80 to 150 parts of solution C; in substance A, the molar ratio of undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, trichloronitrobenzene and 1-methyl-5-nitro-2-hydroxymethylimidazole is (1 to 1.5): (1 to 1.5): 1: 1, the weight of potassium carbonate A is 10 to 15% of the weight of trichloronitrobenzene, and the weight of methanol is 6 to 8 times that of trichloronitrobenzene; the weight of potassium carbonate B is 15 to 25% of the weight of undecyl alcohol.

6. The low dielectric epoxy resin for copper clad laminate according to claim 4, characterized in that: The solution A comprises 1-methyl-5-nitro-2-hydroxymethylimidazole and dichloromethane in a mass ratio of 1:(8-12); the solution B comprises undecyl alcohol, 4-hydroxy-3-tert-butyl-anisole, and propylene glycol in an amount of 8-12 times the total mass of undecyl alcohol and 4-hydroxy-3-tert-butyl-anisole; and the solution C comprises ammonium formate and ethanol in a mass ratio of 1:(4-5).

7. The low dielectric epoxy resin for copper clad laminate according to claim 1, characterized in that: The preparation of the low dielectric filler comprises the following steps: adding hollow glass microspheres to a sodium hydroxide aqueous solution, reflux stirring and reacting for 1 to 2 hours, washing to neutrality, drying, adding an ethanol aqueous solution and an aminosilane coupling agent, stirring at 70 to 80° C. for 4 to 6 hours, filtering, washing with water, and drying to obtain an amino-modified filler; taking the amino-modified filler, acetone, and 1,6-hexanediol diglycidyl ether, mixing them uniformly, reflux reacting for 6 to 8 hours, removing the solvent, washing, and drying to obtain a low dielectric filler.

8. The low dielectric epoxy resin for copper clad laminate according to claim 7, characterized in that: The low dielectric filler comprises the following raw materials, calculated by weight: 10 to 20 parts of amino-modified filler, 100 to 150 parts of acetone, and 3 to 8 parts of 1,6-hexanediol diglycidyl ether; in the amino-modified filler, the added amount of ethanol aqueous solution is 8 to 12 times the mass of hollow glass microspheres, and the added amount of aminosilane coupling agent is 5 to 10% of the mass of hollow glass microspheres; the concentration of hollow glass microspheres in sodium hydroxide aqueous solution is 0.03 to 0.05 mg / mL.

9. A processing technology of low dielectric epoxy resin for copper clad laminate according to any one of claims 1 to 8, characterized in that: The following steps are involved: Take acetone and bisphenol A epoxy resin, mix them evenly, add low dielectric filler, stir evenly to obtain component A; take low dielectric curing agent, curing agent, and curing accelerator, stir for 3 to 5 minutes to obtain component B; add component B to component A, mix evenly, and obtain low dielectric epoxy resin for copper clad laminate.

Citation Information

Patent Citations

  • Aromatic diamine containing imidazolyl and preparation method thereof

    CN102180838A

  • Manufacturing method of low-dielectric-constant CEM-3 copper-clad plate

    CN103419439A

  • Low-dielectric non-fluorine modified polyimide as well as preparation method and application thereof

    CN117701232A

  • Low-dielectric epoxy resin, resin composition for copper-clad plate as well as preparation method and application of resin composition

    CN118406210A

  • Halogen-free low-dielectric resin composition, and prepreg and copper foil laminate made by using same

    US20140154939A1